PRESERFL MicroShunt as a treatment option for highly increased intraocular pressure in primary open angle glaucoma and pseudoexfoliation glaucoma - Theilig, Theresa; Papadimitriou, Menelaos; Meller, Daniel; Hasan, Somar (Eye, 2025)
The Preserflo-MicroShunt (PF) is an established device for treating glaucoma, effectively reducing intraocular pressure (IOP) with a good safety record. However, its efficacy in eyes with significantly elevated preoperative IOP levels is not well-documented due to exclusion from many clinical studies. This study aims to evaluate PF outcomes in eyes with highly increased IOP and compare them with those having moderately increased levels.
Online veröffentlicht: 19. Mai 2025
Gesehen am 21.08.2025